Detection of Diatoms by a Combination of Membrane Filtration and Transparentness1, 2. Issue 6 (10th August 2016) - Zhao, Jian; Wang, Yuzhong; Liu, Chao; Hu, Sunlin; Shi, He; Wen, Jinfeng
Abstract: Diagnosis of drowning remains a difficult issue in current forensic sciences. A large number of diatoms were lost by removing the supernatant after centrifugation in the conventional forensic diatom test. We developed a novel membrane filtration method to enrich diatoms from samples. A new solution using different ratios of acetic acid and eugenol is prepared to make the membrane transparent. These processes allow the diatom‐containing membrane to be visualized and identified easily by light microscopy. The tissues contaminated by water rich in diatoms were detected by the new method for the recovery of diatoms. Eleven drowning cases were analyzed by both the new method and the conventional method to compare the sensitivity of both methods. The recovery of the novel diatom test method was 54.2 ± 23.1%. The positive rate of the novel method has been proven to be superior to the conventional method in the diagnosis of drowning.